Proceedings of the 6th IEEE International Conference on Intelligent Data Acquisition and Advanced Computing Systems 2011
DOI: 10.1109/idaacs.2011.6072756
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of symmetric cryptography in embedded systems

Abstract: We consider the problem of implementing security algorithms into embedded systems deployed in automation applications. Such systems are typically built on embedded microcontrollers with limited resources and as hardware changes may not be possible or convenient, the software based cryptography is a suitable solution. In this paper we present results of performance benchmarks of different software-implemented symmetric cryptography algorithms on 8 and 16-bit microcontroller platforms. The contribution of the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 5 publications
0
15
0
3
Order By: Relevance
“…Therefore, a performance evaluation over constrained platforms of more sophisticated modes like authenticated encryption is relevant since they present significant impact on energy consumption compared to ECB. Additionally, Hyncica et al [12] do not provide energy measurements, which is very important in the context of battery-powered devices. They also do not address the performance behavior when operating systems also play a role.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a performance evaluation over constrained platforms of more sophisticated modes like authenticated encryption is relevant since they present significant impact on energy consumption compared to ECB. Additionally, Hyncica et al [12] do not provide energy measurements, which is very important in the context of battery-powered devices. They also do not address the performance behavior when operating systems also play a role.…”
Section: Related Workmentioning
confidence: 99%
“…In 2011, Hyncica et al [12] evaluated the performance of 15 different block ciphers on three different microcontrollers (of 32-bit, 16-bit, and 8-bit instructions). They used the TomCrypt LTC library version 1.16 which is a general purpose cryptographic library for 32-bit platforms and thus not optimized for constrained microcontrollers.…”
Section: Related Workmentioning
confidence: 99%
“…The encryption and decryption times of AES on various embedded processors are reported in [24] and [25]. In our numerical study we let the data size be 12 000 bits, the encryption time and be 50 ms (assuming an encryption throughput of 300 kbits/s, a constant key setup time of 10 ms on the Texas Instruments MSP430 platform [24], and equal decryption time), the sensing time be 30 ms, the communication time be 40 ms, and the computation time be 30 ms. The normalized results of our numerical study are reported in Fig.…”
Section: An Illustrative Example Consider the Following Model Fomentioning
confidence: 99%
“…Concerning speed records for AES on microcontroller devices, Hyncica in [19] presents optimized AES results of 172 cycles/byte for the MSP430 platform that is based on 32-bit table-based code ported from LibTomCrypt [20]. Gouvea [15] first presented the 16-bit lookup table strategy for AES in which they reported 180 cycles/byte on a MSP430 platform.…”
Section: Related Workmentioning
confidence: 99%